Analisis Perbandingan Pendapatan dan Kesejahteraan Keluarga Karyawan Panen dengan Karyawan Panen dengan Karyawan Perawatan di PT. Socfin Indonesia (SOCFINDO) Kebun Aek-Loba, Kabupaten Asahan Provinsi Sumatera Utara - Riduwan, Muhammad; Purwandari, Istiti; Ambarsari, Arum (AGRIFITIA : Journal of Agribusiness Plantation, 2024)
This study aims to find out 1. The wage system of harvest and maintenance employees at PT Socfindo, 2. Comparison of family income of harvesting and maintenance employees 3. Comparison of family welfare of harvest and maintenance employees at PT. Socfin Indonesia Aek-Loba Plantation. This study used a quantitative method by descriptive. The research location was chosen purposively at PT. Socfin Indonesia Aek-Loba Gardens. Sampling method uses purposive sampling technique and data collection method uses descriptive quantitative or descriptive statistics to determine income comparisons and welfare comparisons between families of harvest employees and families of maintenance employees at PT. Socfin Indonesia Aek-Loba Gardens. The research results obtained are 1. The wage system of harvest and maintenance at PT. Socfin Indonesia Aek-Loba plantations pay system which is given to harvest employees using a time unit system and yield units then maintenance employees use a time unit system. 2. Comparison of family income of harvesting and maintenance employees at PT. Socfin Indonesia Aek-Loba Plantation is a significant difference of IDR 1,227,549. 3. There is no significant difference between the welfare of the families of harvest employees and the maintenance at PT.Socfin Indonesia, Aek Loba Garden, Asahan Regency, North Sumatra.